Challenges and strategic approaches for lean construction implementation: a case study from Malaysia's construction sector - Ahmad Rizal, Alias; Mohammad Adam, Adman; Abdul Qaiyum, Abd Hamid (IOP Science, 2025)
Lean Construction (LC) is an innovative project management strategy that emphasizes efficiency, waste reduction, and continuous improvement in the construction sector. The objectives of this paper are to identify the main challenges and strategies, compare the most relevant challenges and strategies across various organizations, and analyze the relationships among organizations in implementing LC practices. A survey was conducted to gather data from construction professionals. The data collected was subjected to thorough analysis using several methods, such as mean score ranking with normalization, overlap analysis, the Kruskal-Wallis test, and correlation analysis. Key challenges identified include a lack of skills training and lean techniques, a lack of clear definition of individual’s responsibility and a lack of individual performance measurement reward system and motivation. Critical strategies to overcome these issues include a clear definition of client requirements, better health and safety, and effective changes in decision-making mechanisms. Correlation analysis revealed moderate links between challenges, such as teamwork issues, and strategies like the systematic deployment of lean principles. The study concludes that addressing training and knowledge gaps, coupled with managerial commitment, is crucial for implementing LC practices in Malaysia. As the first research to examine overlaps between challenges and strategies among Malaysia’s key stakeholders, this work offers actionable insights to enhance project outcomes while advancing the global discourse on lean adoption in developing economies.